Dielectric, Electromechanical and Elastic Properties of K (NH ) H PO Compounds - Korotkov, L.; Likhovaja, Likhovaja; Levitsky, R.; Zachek, I.; Vdovych, A. (Physics and Chemistry of Solid State, 2015)
We describe the available experimental data for the dielectric, piezoelectric, and elastic characteristics of the antiferroelectric crystals, using the proposed microscopic theory. Within the framework of the thermodynamic theory and using the obtained experimental data we calculate the dielectric, piezoelectrlic, and elastic characteristics of the compounds at > 0.32.